PELAYANAN BUS KAMPUS TERHADAP MAHASISWA UNIVERSITAS RIAU DI PEKANBARU - Fina Mustaina; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to see and find out how the campus bus service to students. The population of this research is Student bus users campuses, research was conducted at the University of Riau Pekanbaru object of study is the Student bus users campus, average per / week as many as 2464 sample of this research is Student bus users campus, method used Quota sampling with consideration average per / day fluctuate, the number of bus stops are in the main, the average bus capacity 3x 90, ability Writer. sample size of this study are 96 students at the University of Riau. Then the data were analyzed using quantitative descriptive. Based on the analysis, it was found that student users Bus dominated by FAPERIKA with percentages26% this is because the farthest distance from the bus ride to reach faculty FAPERIKA and views from the campus bus user forces dominated by force in 2015 with a percentage of 39.58%, this is due to for force generation 2015 is classified as dense lecture schedule, not many peer networks, mostly parents of students have not facilitate private vehicles, therefore the students often use the campus bus for personal use. facilities and infrastructure of the bus to facilities bus by category comfortably as many as 48 people with a percentage of 50%, response facilities stop choosing less comfortable are 72 people with a percentage of 75% due to overcrowding at the shelter, sometimes do not have a place to sit while waiting for the bus to arrive because bus turnaround quite long, and if the rain splash hujan.hal this which causes less comfortable students. We recommend that facilities need to be added/enlarged his stops. for the fleet of bus user states do not need the addition of a fleet of 65 people with a percentage of 67.70%. Student responses to the Operational hour bus stating unfavorable approximately as many as 59 people with a percentage of 61.46%, this is due to a less than optimal operational hours therefore critical operations clock needs to be improved.Keywords : Campus Bus Service, Students